Anti-neuroinflammatory activity of Humulus japonicus extract and its active compound luteolin on lipopolysaccharide-induced inflammatory response in SIM-A9 microglia via NF-κB and MAPK signaling pathways - WANG,Feng (2022)
Abstract Humulus japonicus (HJ) is administered to patients with pulmonary disease and skin disease owing to its anti-inflammatory and antioxidant effects. Lately, HJ has been shown to exert impacts on protection against neurodegenerative sickness. Nevertheless, its impacts on microglia have not been discovered in depth. As a result, anti-inflammatory impacts of HJ ethanol extract (HJE) and its active compound luteolin on lipopolysaccharide-stimulated SIM-A9 cells were investigated. The results showed that HJE luteolin inhibited generation of interleukin-1β, tumor necrosis factor-α, nitric oxide, interleukin-6, together with prostaglandin E2, iNOS, COX-2 along with HO-1 induction. Furthermore, HJE and luteolin reduced degrees of NF-κB pathway components within cytoplasm and nucleus, while reducing cytoplasmic MAPK levels and increasing Nrf2 levels in the cytoplasm and nucleus. In conclusion, our results demonstrate that HJE might exhibit neuroprotective effects and could be used as a novel drug for various neurological diseases.